Solved Problems 1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 6

EEF 210E DIFFERENTIAL EQUATIONS

PROBLEM SET 1

1. Solve the differential equation 𝒚′ − 𝟐𝒚 = 𝒕𝟐 𝒆𝟐𝒕 .

Recall: For first order differential equations in the form of 𝑦 ′ + 𝑝(𝑡)𝑦 = 𝑔(𝑡), a method called
integrating factor that utilize an integrating factor 𝜇(𝑡), which is chosen to represent the left side
of the equation as the derivative of the product term 𝜇(𝑡)𝑦, can be employed to solve equation.

First, multiply both sides by 𝜇(𝑡).


×𝜇(𝑡)
𝑦 ′ − 2𝑦 = 𝑡 2 𝑒 2𝑡 ⇒ 𝜇(𝑡)𝑦 ′ − 2𝜇(𝑡)𝑦 = 𝜇(𝑡)𝑡 2 𝑒 2𝑡
⇒ [𝜇(𝑡)𝑦]′ = 𝜇(𝑡)𝑡 2 𝑒 2𝑡

Then, obtain the value 𝜇(𝑡).


[𝜇(𝑡)𝑦]′ = 𝜇 ′ (𝑡)𝑦 + 𝜇(𝑡)𝑦 ′ = 𝜇(𝑡)𝑦 ′ − 2𝜇(𝑡)𝑦
𝑑𝜇(𝑡) 𝑑𝜇(𝑡)
⇒ 𝜇 ′ (𝑡) = = −2𝜇(𝑡) ⇒ = −2𝑑𝑡
𝑑𝑡 𝜇(𝑡)
𝑑𝜇(𝑡)
⇒ ∫ = ∫ −2𝑑𝑡 ⇒ ln|𝜇(𝑡)| = −2𝑡 ⇒ 𝝁(𝒕) = 𝒆−𝟐𝒕
𝜇(𝑡)

Finally, to find the solution, substitute 𝝁(𝒕) = 𝒆−𝟐𝒕 into the equation.
𝑑[𝑒 −2𝑡 𝑦]
[𝜇(𝑡)𝑦]′ = 𝜇(𝑡)𝑡 2 𝑒 2𝑡 ⇒ = 𝑒 −2𝑡 𝑡 2 𝑒 2𝑡 = 𝑡 2
𝑑𝑡
𝑑[𝑒 −2𝑡 𝑦]
⇒ = 𝑡 2 ⇒ 𝑑[𝑒 −2𝑡 𝑦] = 𝑡 2 𝑑𝑡
𝑑𝑡
𝑡3 𝟏
⇒ ∫ 𝑑[𝑒 −2𝑡 𝑦] = ∫ 𝑡 2 𝑑𝑡 ⇒ 𝑒 −2𝑡 𝑦 = + 𝑘 ⇒ 𝒚 = 𝒕𝟑 𝒆𝟐𝒕 + 𝒌𝒆𝟐𝒕
3 𝟑
2. Solve the differential equation 𝒚′ + 𝒚 = 𝒕 where 𝒚(𝟎) = 𝟐.

Recall: For first order differential equations in the form of 𝑦 ′ + 𝑝(𝑡)𝑦 = 𝑔(𝑡), a method called
integrating factor that utilize an integrating factor 𝜇(𝑡), which is chosen to represent the left side
of the equation as the derivative of the product term 𝜇(𝑡)𝑦, can be employed to solve equation.

First, multiply both sides by 𝜇(𝑡).


×𝜇(𝑡)
𝑦′ + 𝑦 = 𝑡 ⇒ 𝜇(𝑡)𝑦 ′ + 𝜇(𝑡)𝑦 = 𝜇(𝑡)𝑡
⇒ [𝜇(𝑡)𝑦]′ = 𝜇(𝑡)𝑡

Second, obtain the value 𝜇(𝑡).


𝑑[𝜇(𝑡)𝑦]
= 𝜇′(𝑡)𝑦 + 𝜇(𝑡)𝑦 ′ = 𝜇(𝑡)𝑦 ′ + 𝜇(𝑡)𝑦
𝑑𝑡
𝑑𝜇(𝑡) 𝑑𝜇(𝑡)
⇒ 𝜇 ′ (𝑡) = = 𝜇(𝑡) ⇒ = 𝑑𝑡
𝑑𝑡 𝜇(𝑡)
𝑑𝜇(𝑡)
⇒ ∫ = ∫ 𝑑𝑡 ⇒ ln|𝜇(𝑡)| = 𝑡 ⇒ 𝝁(𝒕) = 𝒆𝒕
𝜇(𝑡)

Then, to find the solution, substitute 𝝁(𝒕) = 𝒆𝒕 into the equation.


𝑑[𝑒 𝑡 𝑦]
[𝜇(𝑡)𝑦]′ = 𝜇(𝑡)𝑡 ⇒ = 𝑒𝑡𝑡
𝑑𝑡
𝑑[𝑒 𝑡 𝑦] integrate
⇒ = 𝑒 𝑡 𝑡 ⇒ 𝑑[𝑒 𝑡 𝑦] = 𝑒 𝑡 𝑡𝑑𝑡 ⇒ ∫ 𝑑[𝑒 𝑡 𝑦] = ∫ 𝑒 𝑡 𝑡𝑑𝑡
𝑑𝑡
Apply integration by parts ∫ 𝑢𝑑𝑣 = 𝑢𝑣 − ∫ 𝑣𝑑𝑢 by choosing 𝑢 = 𝑡, 𝑑𝑣 = 𝑒 𝑡 𝑑𝑡, 𝑣 = 𝑒 𝑡 , 𝑑𝑢 = 𝑑𝑡
to calculate ∫ 𝑒 𝑡 𝑡𝑑𝑡.

⇒ ∫ 𝑒 𝑡 𝑡𝑑𝑡 = 𝑡𝑒 𝑡 − ∫ 𝑒 𝑡 𝑑𝑡 ⇒ ∫ 𝒆𝒕 𝒕𝒅𝒕 = 𝒕𝒆𝒕 − 𝒆𝒕 + 𝒌

⇒ ∫ 𝑑[𝑒 𝑡 𝑦] = ∫ 𝑒 𝑡 𝑡𝑑𝑡 ⇒ 𝑒 𝑡 𝑦 = 𝑡𝑒 𝑡 − 𝑒 𝑡 + 𝑘 ⇒ 𝒚 = 𝒕 − 𝟏 + 𝒌𝒆−𝒕

Finally, plug the initial value 𝒚(𝟎) = 𝟐 at time 𝒕 = 𝟎 in the equation to obtain solution.
𝑦(0) = 2 = 0 − 1 + 𝑘𝑒 −0 ⇒ 𝑘 − 1 = 2 ⇒ 𝒌 = 𝟑
⇒ 𝒚 = 𝒕 − 𝟏 + 𝟑𝒆−𝒕
3. Solve the differential equation given below.
𝟑𝒙𝟐 + 𝟒𝒙 − 𝟒
𝒚′ = , 𝒚(𝟏) = 𝟑
𝟐𝒚 − 𝟒

Recall: The equation is linear and separable. Therefore, the 𝑦 and 𝑥 terms should be separated on
different sides to obtain an implicit solution.

First, separate the 𝑦 and 𝑥 terms.


𝑑𝑦 3𝑥 2 + 4𝑥 − 4
= ⇒ (2𝑦 − 4)𝑑𝑦 = (3𝑥 2 + 4𝑥 − 4)𝑑𝑥
𝑑𝑥 2𝑦 − 4

⇒ ∫(2𝑦 − 4)𝑑𝑦 = ∫(3𝑥 2 + 4𝑥 − 4)𝑑𝑥 ⇒ 𝒚𝟐 − 𝟒𝒚 = 𝒙𝟑 + 𝟐𝒙𝟐 − 𝟒𝒙 + 𝒌

Then, to find 𝑘, plug 𝒚(𝟏) = 𝟑 value at time 𝒙 = 𝟏 in the equation.


⇒ 32 − 4 ⋅ 3 = 13 + 2 ⋅ 12 − 4 ⋅ 1 + 𝑘 ⇒ 𝑘 − 1 = −3 ⇒ 𝒌 = −𝟐
Substitute 𝑐 = −2 value into the equation to obtain implicit solution.
⇒ 𝒚𝟐 − 𝟒𝒚 = 𝒙𝟑 + 𝟐𝒙𝟐 − 𝟒𝒙 − 𝟐

Finally, to obtain the explicit solution, the discriminant method can be used after rewriting the
equation as a second order polynomial.
𝑦 2 − 4𝑦 = 𝑥 3 + 2𝑥 2 − 4𝑥 − 2 ⇒ 𝒚𝟐 − 𝟒𝒚 − 𝒙𝟑 − 𝟐𝒙𝟐 + 𝟒𝒙 + 𝟐 = 𝟎
For a = 1, b = −4, and c = −x 3 − 2x 2 + 4x + 2, the discriminant value will be b2 − 4ac. Thus,
the explicit solution(s) can be obtained as follows.
−b ± √b 2 − 4ac 𝟒 ± √𝟏𝟔 + 𝟒𝒙𝟑 + 𝟖𝒙𝟐 − 𝟏𝟔𝒙 − 𝟖
𝑦= ⇒ 𝒚=
2a 𝟐

4.
5. Solve the differential equation below.
(𝒆𝒙 𝐬𝐢𝐧 𝒚 − 𝟐𝒚 𝐬𝐢𝐧 𝒙)𝒅𝒙 + (𝒆𝒙 𝐜𝐨𝐬 𝒚 + 𝟐 𝐜𝐨𝐬 𝒙)𝒅𝒚 = 𝟎

Recall: The differential equations in the form of 𝑀𝑑𝑥 + 𝑁𝑑𝑦 = 0 are called as exact equations if
𝑑𝑀/𝑑𝑦 = 𝑑𝑁/𝑑𝑥. For exact equations, solution may be obtained via ∫ 𝑀 𝑑𝑥 = ∫ 𝑁 𝑑𝑦 equality.

First, check if the equation is exact.


𝑀𝑑𝑥 + 𝑁𝑑𝑦 = (𝑒 𝑥 sin 𝑦 − 2𝑦 sin 𝑥)𝑑𝑥 + (𝑒 𝑥 cos 𝑦 + 2 cos 𝑥)𝑑𝑦 = 0
𝑑𝑀
𝑀 = 𝑒 𝑥 sin 𝑦 − 2𝑦 sin 𝑥 ⇒ = 𝑒 𝑥 cos 𝑦 − 2 sin 𝑥 𝒅𝑴 𝒅𝑵
𝑑𝑦
⇒ = (exact equation)
𝑥
𝑑𝑁 𝑥
𝒅𝒚 𝒅𝒙
𝑁 = 𝑒 cos 𝑦 + 2 cos 𝑥 ⇒ = 𝑒 cos 𝑦 − 2 sin 𝑥 }
𝑑𝑥

Then, calculate ∫ 𝑀 𝑑𝑥 = ∫ 𝑁 𝑑𝑦.

∫ 𝑀 𝑑𝑥 = ∫(𝑒 𝑥 sin 𝑦 − 2𝑦 sin 𝑥)𝑑𝑥 ⇒ 𝑒 𝑥 sin 𝑦 + 2𝑦 cos 𝑥 + ℎ(𝑦)


ℎ(𝑥) = 0
} ⇒ {
ℎ(𝑦) =0
∫ 𝑁 𝑑𝑦 = ∫(𝑒 𝑥 cos 𝑦 + 2 cos 𝑥)𝑑𝑦 ⇒ 𝑒 𝑥 sin 𝑦 + 2𝑦 cos 𝑥 + ℎ(𝑥)

assume 𝑘=0 sin 𝑦


⇒ 𝒆𝒙 𝐬𝐢𝐧 𝒚 + 𝟐𝒚 𝐜𝐨𝐬 𝒙 = 𝒌 ⇒ = −2𝑒 −𝑥 cos 𝑥
𝑦

⇒ 𝐬𝐢𝐧𝐜 𝒚 = −𝟐𝒆−𝒙 𝐜𝐨𝐬 𝒙


6.
7. Solve the differential equation below.
𝒚 𝒚
𝒚′ = + 𝐭𝐚𝐧 ( )
𝒙 𝒙

Recall: A differential equation in the form of 𝑑𝑦/𝑑𝑥 = 𝑓(𝑦/𝑥) is called homogeneous differential
equation if it depends on only 𝑦/𝑥 term and its derivatives.

The given differential equation only depends on 𝑦/𝑥 terms and its first derivative. Therefore, it is
a first order homogeneous differential equation. So, to solve it, substitution can be used.

Let 𝑦 = 𝑣𝑥. Write 𝑦 ′ in terms of 𝑣 and 𝑥 and substitute into the equation.
𝑑𝑦 𝑑𝑣
𝑦′ = = 𝑥+𝑣 𝑑𝑣 𝑑𝑣
𝑑𝑥 𝑑𝑥 } ⇒ 𝑥 + 𝑣 = 𝑣 + tan 𝑣 ⇒ 𝑥 = tan 𝑣
𝑦 𝑦 𝑑𝑥 𝑑𝑥
𝑦 ′ = + tan ( )
𝑥 𝑥
𝑑𝑣 𝑑𝑣 𝑑𝑥
⇒ 𝑥 = tan 𝑣 ⇒ =
𝑑𝑥 tan 𝑣 𝑥

Then, integrate both sides of the equation to find solution for 𝑣.


𝑑𝑣 𝑑𝑥
⇒ ∫ =∫ ⇒ ln|sin 𝑣| = ln|𝑥| + 𝑘 ⇒ sin 𝑣 = 𝑒 𝑘 𝑥
tan 𝑣 𝑥
⇒ sin 𝑣 = 𝑒 𝑘 𝑥 ⇒ 𝒗 = 𝐚𝐫𝐜𝐬𝐢𝐧(𝒆𝒌 𝒙)

Finally, resubstitute 𝑣 = 𝑦/𝑥 into the equation to obtain solution for y.


𝑦
⇒ = arcsin(𝑒 𝑘 𝑥) ⇒ 𝒚 = 𝒙 𝐚𝐫𝐜𝐬𝐢𝐧(𝒆𝒌 𝒙)
𝑥

You might also like